Study of pathological changes associated with Eimeria Acervulina infection in broiler chickens in Hama (Journal of Hama University, 2022)
Coccidiosis in chickens is one of the most common and widespread diseases of poultry. Coccidiosis can lead to serious economic losses due to elevated morbidity and mortality and low feed conversion ratio as a result of inflammation and damages to the intestinal mucosa. E. acervulina is one type of Eimeria diseases in broiler chickens. The infection spreads all over the world, which usually causes subclinical infection, and there are cases of mucous watery diarrhea, accompanied by a decrease in the rate of weight gain.The study was conducted on 20 flocks of broiler chickens at age ranged between 20-45 days. One hundred twenty samples were collected from the duodenal of the infected chickens in order to study the severity of the pathological changes caused by Eimeria acervulina infection. Lesions were characterized by the presence of white spots scattered in the duodenum, With thickening of its walls in severe infection.Histopathology study of duodenum revealsed a large clusters of schizonts and oocysts submucosa and lamina propria crowded with.There were often,large areas of the mucosa sloughed off mucosa. Scores of infection were divided into four degrees according to the severity of the infection.It was noted that the highest incidence of infection was score (3) 37.5%, followed by score (4) 30.83%, followed by (2) 19.16%, and finally score (1) 12.5% which was the lowest according to severity of changes and observations.This study showed that score (3) and score (4) were the most frequent, This is an indication that most of the infection is subclinical and often treatment is late.